A wear-resistant and corrosion-resistant gradient coating on the surface of a reactor and a preparation method thereof

By preparing ZrO2 gradient coatings using electrospark deposition technology, the problems of large coating roughness and poor process repeatability on the reactor surface were solved, achieving coating effects with high wear resistance, corrosion resistance and long service life.

CN116716607BActive Publication Date: 2025-01-07YUNNAN TIN INDIUM LAB CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310679138.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2025-01-07
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

Existing technologies for preparing coatings on the surface of reaction vessels suffer from problems such as high surface roughness of the film, particle encapsulation leading to peeling failure, affecting wear resistance, poor process repeatability, and reduced equipment lifespan.

Method used

A ZrO2 gradient coating was prepared using electrical discharge deposition (EDD). By controlling the grain size and electrode parameters, multiple gradient layers with different grain sizes were formed. The total coating thickness was 100-300 nm, including coarse-grained, fine-grained, and ultrafine-grained regions. The coating exhibited high bonding strength and prevented it from peeling off.

Benefits of technology

It improves the wear and corrosion resistance of the reactor surface, extends the service life of the equipment, and has a fast deposition rate, good film density, high bonding strength, and is not easy to fall off.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116716607B_ABST
    Figure CN116716607B_ABST
Patent Text Reader

Abstract

The present invention discloses a wear-resistant and corrosion-resistant gradient coating on the surface of a reactor and a preparation method thereof, and belongs to the technical field of wear-resistant coating preparation. The present invention adopts an electrospark deposition technology to prepare a wear-resistant and corrosion-resistant coating of ZrO2 on the surface of a common reactor material, and the wear-resistant and corrosion-resistant gradient coating has multiple gradient layers with different densities; nickel powder and zirconium dioxide powder are mixed and sintered to form an electrode, the mass ratio of nickel powder to zirconium dioxide and the particle size of zirconium dioxide powder are controlled, and an electrospark deposition technology is adopted to form a wear-resistant and corrosion-resistant gradient coating on the surface of the reactor substrate; the present invention has a short preparation cycle and a dense coating, and can meet the wear resistance and corrosion resistance of the reactor substrate in a harsh working environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a wear-resistant and corrosion-resistant gradient coating on the surface of a reactor and a preparation method thereof, belonging to the technical field of wear-resistant coating preparation. Background Art

[0002] The broad understanding of a reactor is a container for physical or chemical reactions. Through the structural design and parameter configuration of the container, the heating, evaporation, cooling and low-speed mixing functions required by the process can be achieved. Reactors often work in high-temperature and highly corrosive environments. In addition, the reactants will wear the inner wall of the reactor to a certain extent under the action of the agitator. Working under highly corrosive and high-wear conditions will greatly reduce the life of the reactor. For example, in tin chemical production, the solid is mainly refined tin raw materials, and the liquid is some acidic or alkaline raw materials that are used to prepare metastannic acid under heating conditions. The reactor material used is zirconium. Through research, it is found that the zirconium-based surface will oxidize to form ZrO2 under high temperature conditions. The oxide layer has good corrosion and wear resistance. However, the mechanical mismatch between the zirconium base and the oxide layer will affect the bonding strength between the oxide layer and the substrate, which will aggravate the loss of the reactor material after long-term corrosion and wear.

[0003] Traditional methods for preparing coatings include vacuum evaporation, ion plating, magnetron sputtering and electrochemical deposition. Ion plating will deposit larger particles (5-10μm) on the surface of the workpiece, resulting in a larger surface roughness of the film. Some particles will be wrapped in the plated film, which may easily cause the film to peel off and fail during long-term use, affecting the wear resistance of the film and greatly reducing the service life of the equipment. Vacuum evaporation is not easy to obtain a thin film with a crystalline structure, and the process repeatability is not good enough. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant and corrosion-resistant ZrO2 gradient coating with a gradient structure, wherein the target material of the wear-resistant and corrosion-resistant gradient coating on the surface of the reactor is ZrO2, and the wear-resistant and corrosion-resistant gradient coating comprises multiple layers of gradient layers with different grain sizes, and the total thickness of the gradient coating is 100-300nm, which is divided into coarse grain zone, fine grain zone and ultrafine grain zone according to the grain size, and the thickness of each gradient is controlled to be 30-100nm.

[0005] Another object of the present invention is to provide a method for preparing the wear-resistant and corrosion-resistant gradient coating on the surface of the reactor, which specifically comprises the following steps:

[0006] (1) The surface of the reactor substrate is pretreated to ensure that there are no pollutants or rust spots on the surface. The surface of the substrate is flat and the roughness is Ra0.1 or below.

[0007] (2) Nickel powder and zirconium dioxide of different particle sizes are mixed in a mass ratio of (30-40):(60-70), and pressed and sintered into an electrode.

[0008] (3) The sintered electrode is processed into a round rod shape, and the surface is mechanically ground and polished, and the surface oil and rust spots are removed by ultrasonic cleaning.

[0009] (4) Before electrospark deposition, the electrode is fixed on the gun head fixture, the reactor substrate is fixed on the workbench, the electrode is connected to the anode, the processed substrate material is connected to the cathode, and argon gas is introduced for protection.

[0010] (5) The reactor is subjected to three repeated electrospark deposition techniques, and electrodes of three grades, 5-15 μm, 20-30 μm, and 35-50 μm, are selected in turn to prepare a gradient wear-resistant and corrosion-resistant coating; the reactor substrate after the wear-resistant and corrosion-resistant gradient coating is formed on the surface is immersed in acetone, cleaned and dried, and the dried reactor substrate is vacuum sealed and stored.

[0011] Preferably, the reaction kettle substrate of the present invention is one of carbon manganese steel, stainless steel, zirconium and nickel-based alloy.

[0012] Preferably, the surface pretreatment method of the present invention is to polish the surface of the substrate with 80-1500 mesh metallographic sandpaper, and after polishing, use anhydrous ethanol or acetone as a solvent to perform ultrasonic decontamination cleaning and drying.

[0013] Preferably, in step (2) of the present invention, the pressing pressure is 30-45 MPa, and the sintering temperature and time are 900-1000° C. and 30-40 min, respectively.

[0014] Preferably, the specific process parameters of the electrospark deposition technology described in the present invention are: power: 900-1200W, argon gas flow: 15-20L / min, electrode rotation rate: 3000-4000r / min, and deposition time per unit area: 1-2cm / min.

[0015] The technical effects of the present invention are:

[0016] The present invention controls the growth of ZrO2 film by adjusting parameters such as the ratio of composite electrode materials, grain size, and electric spark technology, optimizes the film structure, and forms a wear-resistant and corrosion-resistant film with a gradient distribution of grain size. The gradient-distributed coating improves the interface bonding strength, making the coating less likely to fall off in a working environment, thereby improving the wear resistance and corrosion resistance and extending the service life. In addition, this method has a fast deposition speed and a short preparation cycle. No large particles will appear on the film surface, and the density of the entire gradient layer is good.

[0017] The present invention uses electric spark deposition technology, which has a small heat input and little impact on the substrate, but can obtain excellent metallurgical bonding ability with the substrate; by controlling the particle size, the uniformity of deposition is improved, thereby avoiding premature peeling of the coating and affecting the wear resistance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the manufacturing method of an embodiment of the present invention.

[0019] Figure 2 This is a structural diagram of the wear-resistant and corrosion-resistant gradient coating of an embodiment of the present invention.

[0020] Figure 3 This is a scanning electron microscope image of a cross section of the wear-resistant and corrosion-resistant gradient coating according to an embodiment of the present invention.

[0021] Figure 4 This is a scanning electron microscope image of the surface of the wear-resistant and corrosion-resistant gradient coating according to an embodiment of the present invention. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0023] Example 1

[0024] A wear-resistant and corrosion-resistant gradient coating on the surface of a reactor and a preparation method thereof, such as Figure 1 As shown, the specific steps include:

[0025] (1) Pre-treat the zirconium substrate by grinding the substrate surface with 80-1500 mesh metallographic sandpaper. After grinding, use anhydrous ethanol or acetone as a solvent to perform ultrasonic cleaning and drying to remove surface pollutants and rust spots.

[0026] (2) Place the pretreated reactor substrate into a vacuum chamber with a vacuum degree of 1×10 -1 Pa, the atmosphere is argon with a purity of 99.90%, and the substrate surface is vacuum ion cleaned.

[0027] (3) Nickel powder and zirconium dioxide powder (the mass ratio of nickel powder to zirconium dioxide is 30:70) are selected and pressed and sintered into electrode materials, and the particle size of zirconium dioxide is controlled to be three levels of 5-15 μm, 20-30 μm, and 35-50 μm. The sintering temperature is selected to be 950 ° C, the pressing pressure is controlled to be 40 MPa, and the sintering time is 35 min.

[0028] (4) Process the sintered electrode into a round rod shape, and polish the electrode with 80-1500 mesh metallographic sandpaper. After polishing, use anhydrous ethanol or acetone as a solvent to perform ultrasonic cleaning and dry to remove surface pollutants and rust spots.

[0029] (5) The first electrospark deposition was carried out under argon protection with a power of 950 W, an argon flow rate of 15 L / min, an electrode rotation rate of 3000 r / min, and a deposition time per unit area of ​​1 cm / min. A composite electrode made of 5-15 μm was selected for this deposition, and a layer of fine grains with a thickness of 50 nm was deposited on the zirconium substrate.

[0030] (6) After the first electrospark deposition, the electrode was replaced and the second electrospark deposition was carried out under argon protection with a power of 1000 W, an argon flow rate of 15 L / min, an electrode rotation rate of 3500 r / min, and a deposition time per unit area of ​​1.2 cm / min. A composite electrode made of 20-30 μm was selected for this deposition, and a fine grain area with a thickness of 50 nm was deposited on the zirconium substrate.

[0031] (7) After the second electrospark deposition, the electrode was replaced and the third electrospark deposition was carried out under argon protection with a power of 1100 W, an argon flow rate of 20 L / min, an electrode rotation rate of 3500 r / min, and a deposition time per unit area of ​​1.5 cm / min. A composite electrode made of 35-50 μm was selected for this deposition, and a coarse grain area with a thickness of 50 nm was deposited on the zirconium substrate.

[0032] (8) End the electrospark deposition and turn off the device.

[0033] The wear-resistant and corrosion-resistant gradient coating obtained in this embodiment comprises multiple gradient layers with different grain sizes, and the total thickness of the gradient coating is 150 nm.

[0034] Figure 3 , Figure 4 They are the cross-section and surface scanning electron microscope pictures of the wear-resistant and corrosion-resistant gradient coating respectively. It can be seen from the figures that the wear-resistant and corrosion-resistant gradient coating is tightly bonded to the reactor substrate and the coating thickness is within 300nm. The grain size increases from bottom to top; there are no obvious defects on the coating surface, indicating that the coating has excellent deposition performance and can meet the wear-resistant and corrosion-resistant working conditions of the reactor.

[0035] The gradient coating prepared in the embodiment of the present invention has good bonding with the substrate. The tested interface bonding strength reaches 65 MPa, which exceeds the bonding strength of most coatings and is not easy to fall off.

[0036] Example 2

[0037] A wear-resistant and corrosion-resistant gradient coating on the surface of a reactor and a preparation method thereof, such as Figure 1 As shown, the specific steps include:

[0038] (1) Pre-treat the zirconium substrate by grinding the substrate surface with 80-1500 mesh metallographic sandpaper. After grinding, use anhydrous ethanol or acetone as a solvent to perform ultrasonic cleaning and drying to remove surface pollutants and rust spots.

[0039] (2) Place the pretreated reactor substrate into a vacuum chamber with a vacuum degree of 1×10 -1 Pa, the atmosphere is argon with a purity of 99.90%, and the substrate surface is vacuum ion cleaned.

[0040] (3) Nickel powder and zirconium dioxide powder (the mass ratio of nickel powder to zirconium dioxide is 40:60) are selected and pressed and sintered into electrode materials, and the particle size of zirconium dioxide is controlled to be three levels of 5-15 μm, 20-30 μm, and 35-50 μm. The sintering temperature is selected to be 1000 °C, the pressing pressure is controlled to be 30 MPa, and the sintering time is 30 min.

[0041] (4) Process the sintered electrode into a round rod shape, and polish the electrode with 80-1500 mesh metallographic sandpaper. After polishing, use anhydrous ethanol or acetone as a solvent to perform ultrasonic cleaning and dry to remove surface pollutants and rust spots.

[0042] (5) The first electrospark deposition was carried out under argon protection with a power of 900 W, an argon flow rate of 18 L / min, an electrode rotation rate of 4000 r / min, and a deposition time per unit area of ​​2 cm / min. A composite electrode made of 5-15 μm was selected for this deposition, and a layer of fine grains with a thickness of 30 nm was deposited on the zirconium substrate.

[0043] (6) After the first electrospark deposition, the electrode was replaced and the second electrospark deposition was carried out under argon protection with a power of 900 W, an argon flow rate of 20 L / min, an electrode rotation rate of 3000 r / min, and a deposition time per unit area of ​​1.2 cm / min. A composite electrode made of 20-30 μm was selected for this deposition, and a fine grain area with a thickness of 70 nm was deposited on the zirconium substrate.

[0044] (7) After the second electrospark deposition, the electrode was replaced and the third electrospark deposition was carried out under argon protection, with a power of 1100 W, an argon flow rate of 20 L / min, an electrode rotation rate of 3500 r / min, and a deposition time per unit area of ​​1.5 cm / min. A composite electrode made of 35-50 μm was selected for this deposition, and a coarse grain area with a thickness of 100 nm was deposited on the zirconium substrate.

[0045] (8) End the electrospark deposition and turn off the device.

[0046] The wear-resistant and corrosion-resistant gradient coating obtained in this embodiment comprises multiple gradient layers with different grain sizes, and the total thickness of the gradient coating is 200 nm.

[0047] The gradient coating prepared in the embodiment of the present invention has good bonding with the substrate. The tested interface bonding strength reaches 63 MPa, which exceeds the bonding strength of most coatings and is not easy to fall off.

[0048] Example 3

[0049] A wear-resistant and corrosion-resistant gradient coating on the surface of a reactor and a preparation method thereof, such as Figure 1 As shown, the specific steps include:

[0050] (1) Pre-treat the zirconium substrate by grinding the substrate surface with 80-1500 mesh metallographic sandpaper. After grinding, use anhydrous ethanol or acetone as a solvent to perform ultrasonic cleaning and drying to remove surface pollutants and rust spots.

[0051] (2) Place the pretreated reactor substrate into a vacuum chamber with a vacuum degree of 1×10 -1 Pa, the atmosphere is argon with a purity of 99.90%, and the surface of the substrate is vacuum ion cleaned.

[0052] (3) Nickel powder and zirconium dioxide powder (the mass ratio of nickel powder to zirconium dioxide is 35:65) are selected and pressed and sintered into electrode materials, and the particle size of zirconium dioxide is controlled to be three levels of 5-15 μm, 20-30 μm, and 35-50 μm. The sintering temperature is selected to be 900 °C, the pressing pressure is controlled to be 45 MPa, and the sintering time is 40 min.

[0053] (4) Process the sintered electrode into a round rod shape, and polish the electrode with 80-1500 mesh metallographic sandpaper. After polishing, use anhydrous ethanol or acetone as a solvent to perform ultrasonic cleaning and dry to remove surface pollutants and rust spots.

[0054] (5) The first electrospark deposition was carried out under argon protection, with a power of 1200 W, an argon flow rate of 20 L / min, an electrode rotation rate of 3500 r / min, and a deposition time per unit area of ​​1 cm / min. A composite electrode made of 5-15 μm was selected for this deposition, and a layer of fine grains with a thickness of 60 nm was deposited on the zirconium substrate.

[0055] (6) After the first electrospark deposition, the electrode was replaced and the second electrospark deposition was carried out under argon protection with a power of 1200 W, an argon flow rate of 18 L / min, an electrode rotation rate of 3500 r / min, and a deposition time per unit area of ​​1.2 cm / min. A composite electrode made of 20-30 μm was selected for this deposition, and a fine grain area with a thickness of 50 nm was deposited on the zirconium substrate.

[0056] (7) After the second electrospark deposition, the electrode was replaced and the third electrospark deposition was carried out under argon protection with a power of 1100 W, an argon flow rate of 20 L / min, an electrode rotation rate of 4000 r / min, and a deposition time per unit area of ​​1.5 cm / min. A composite electrode made of 35-50 μm was selected for this deposition, and a coarse grain area with a thickness of 120 nm was deposited on the zirconium substrate.

[0057] (8) End the electrospark deposition and turn off the device.

[0058] The wear-resistant and corrosion-resistant gradient coating obtained in this embodiment comprises multiple gradient layers with different grain sizes, and the total thickness of the gradient coating is 230 nm.

[0059] The gradient coating prepared in the embodiment of the present invention has good bonding with the substrate. The tested interface bonding strength reaches 60 MPa, which exceeds the bonding strength of most coatings and is not easy to fall off.

Claims

1. A method for preparing a wear-resistant and corrosion-resistant gradient coating on the surface of a reactor, characterized in that: The wear-resistant and corrosion-resistant gradient coating comprises multiple layers of gradient layers with different grain sizes, the total thickness of the gradient coating is 100-300nm, and is divided into a coarse grain region, a fine grain region and an ultrafine grain region according to the grain size, and the thickness of each gradient is controlled to be 30-100nm; specifically comprising the following steps: (1) The surface of the reactor substrate is pretreated to ensure that there are no pollutants or rust spots on the surface. The surface of the substrate is flat and the roughness is Ra0.1 or below. (2) Mix nickel powder and zirconium dioxide in a mass ratio of (30-40):(60-70), with the particle size of zirconium dioxide being 5-15 μm, 20-30 μm, and 35-50 μm, and press and sinter them to obtain three electrodes; (3) Processing the sintered electrode into a round rod shape, mechanically grinding and polishing the surface, and ultrasonic cleaning to remove surface oil and rust spots; (4) Before electrospark deposition, fix the electrode on the gun head fixture, fix the reactor substrate on the workbench, connect the electrode to the anode, connect the processed substrate material to the cathode, and introduce argon gas for protection; (5) The electrospark deposition technique was repeated three times on the reactor, and electrodes of three grades, 5-15 μm, 20-30 μm, and 35-50 μm, were selected in turn to prepare a gradient wear-resistant and corrosion-resistant coating.

2. The method for preparing the wear-resistant and corrosion-resistant gradient coating on the surface of the reactor according to claim 1, characterized in that: The reactor base material is one of carbon manganese steel, stainless steel, zirconium and nickel-based alloy.

3. The method for preparing the wear-resistant and corrosion-resistant gradient coating on the surface of the reactor according to claim 2, characterized in that: The surface pretreatment method comprises the following steps: grinding the surface of the substrate with 80-1500 mesh metallographic sandpaper, and after grinding, using anhydrous ethanol or acetone as a solvent to perform ultrasonic decontamination cleaning and drying.

4. The method for preparing the wear-resistant and corrosion-resistant gradient coating on the surface of the reactor according to claim 1, characterized in that: In step (2), the pressing pressure is 30-45 MPa, and the sintering temperature and time are 900-1000°C and 30-40 min, respectively.

5. The method for preparing the wear-resistant and corrosion-resistant gradient coating on the surface of the reactor according to claim 1, characterized in that: The specific process parameters of electrospark deposition technology are: power: 900-1200W, argon gas flow: 15-20L / min, electrode rotation rate: 3000-4000r / min, and deposition time per unit area: 1-2cm / min.

6. The method for preparing the wear-resistant and corrosion-resistant gradient coating on the surface of the reactor according to claim 1, characterized in that: The reactor substrate with the wear-resistant and corrosion-resistant gradient coating formed on the surface is immersed in acetone, cleaned and dried, and the dried reactor substrate is vacuum-sealed and stored.

7. The wear-resistant and corrosion-resistant gradient coating on the surface of the reactor prepared by the method of claim 1.

Citation Information

Patent Citations

  • Method for multiple laser cladding of composite ceramic gradient coating layer on surface of niobium alloy

    CN106435566A

  • Zirconium oxide false tooth with bioactivity

    CN107374763A